Odpowiedzi

2010-03-27T14:27:03+01:00
A) 4x-3=3x+5
x=8

b) 5x+2=7-3x
8x=5
x=5/8

c) 3(x-1)=0
3x-3=0
3x=3
x=1

d)-6(x+1)=24
-6x-6=24
-6x=30
x=-5

e)-7(x-2)=3x-1
-7x+14=3x-1
-10x=-13
x=13/10

f) 4(x-1)=6(1+x)
4x-4=6+6x
-2x=10
x=-5
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-27T14:28:28+01:00
A) 4x-3=3x+5
4x-3x=3+5
x=8

b) 5x+2=7-3x
5x+3x=7-2
8x=5 / :8
x=5/8

c) 3(x-1)=0
3x-3=0
3x=3 /;3
x=1

d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 / : -6
x= -5

e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10x=-15 / :-10
x=1,5

f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=4+6
-2x=10 /: -2
x=-5
2010-03-27T14:39:46+01:00